A fuzzy set scale approach to value workers participation and learning - Milagros Isabel Cova; Carlos Rodríguez Monroy (Journal of Innovation & Knowledge (JIK), 2016)
This article reports the process of building a fuzzy set scale in order to value workers participation and their learning through a technical improvement project in metallurgical plants. The process starts with a practical question which stems from workers: "How can we value our own participation in collective improvement project and the learning related to it?" Participation is structured in three subsets: participation in planning, in designing and in implementing the improvement project. These three subsets are aggregated in a global participation set. Learning is structured in two subsets: individual and group learning in the form of fuzzy inference system Mandami type. Participation (causal condition) constitutes a subset of achieved learning (the outcome), a sufficient but not necessary condition for the outcome. This subset relation is highly consistent providing support for the statement "participatory projects enable meaningful learning" between workers and organization.
Keywords: D70; D83; J24; M10; O35; 650; Workers participation; Collective learning; Fuzzy set; Knowledge sharing